The Implementation of PWA (Progressive Web App) Technology in Enhancing Website Performance & Mobile Accessibility - Ahyar Muawwal (Buletin Pos dan Telekomunikasi, 2024)
The implementation of PWA as a necessary feature aims to provide added value and enhance website performance. This is intended to address several common issues in websites, such as limitations in displaying pages offline and the cost of developing native applications across various operating system platforms, both for desktop and mobile devices. Data collection methods involve literature studies and direct measurements using various tools. Testing conducted includes installation testing, evaluation of PWA criteria, performance, size of transferred resources, and offline mode. Components used in PWA include the web app manifest, service worker, and cache storage. PWA implementation involves creating a web app manifest, service worker registration, service worker configuration, adding script tags, creating specific routes within the website using Express.js, and PWA testing. Test results indicate that the website can be installed and used effectively on various types of devices, both mobile and desktop, and can be accessed in offline mode or with unstable connections.